2002
DOI: 10.1046/j.1471-8286.2002.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 22 microsatellites loci from the endangered Houbara bustard (Chlamydotis undulata undulata)

Abstract: Here we present a new set of 22 microsatellite loci isolated from Chlamydotis undulata undulata, an endangered Houbara bustard found across North Africa. The number of alleles per locus ranged from one to nine, and heterozygosities ranged from 0.167 to 0.944. Total exclusionary probabilities using these loci for the first and the second parent were 0.992932 and 0.999915, respectively. Successful cross‐amplification was observed in eight other Otididae species (12–22 of the 22 loci). These microsatellite marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Library construction and primer design were done by Genetic Identification Service Inc. (USA) as described in Chbel et al (2002). From 1993 to 2007, the three Houbara bustard subspecies were sampled from the 10 different locations listed in Figure 1 and Table 1 avoiding the sampling of close related individuals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Library construction and primer design were done by Genetic Identification Service Inc. (USA) as described in Chbel et al (2002). From 1993 to 2007, the three Houbara bustard subspecies were sampled from the 10 different locations listed in Figure 1 and Table 1 avoiding the sampling of close related individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Dawson et al (1999) while performing analysis on the CHD-Z gene, confirmed the absence of size difference products between two Houbara bustard populations from Morocco and the Canary Islands. Lesobre et al (2010) used both mtDNA and DNA microsatellites as described in Idaghdour et al (2004) and Chbel et al (2002), respectively, and did not find solid evidence of structuring within Cuu either. Pitra et al (2004) studied the macqueenii population history and showed weak structuring using only four microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used Qiagen DNA Blood and Tissue kits to extract DNA and 17 microsatellite loci were amplified using fluorescent primers: loci A2, A10, A21, A22, A29, A106, A120, A204, A205, A210, D12, D110, D118, D119 (Chbel et al 2002), O26 (Lieckfeldt et al 2001) and O27, O38 (Pitra et al 2004). PCR mixtures contained 0.5 U DNA Polymerase (Solis Biodyne), 80 mM Tris-HCl (pH 9.5), 20 mM (NH 4 ) 2 SO 4 , 2.5 mM MgCl 2 , 200 lM dNTPs, 2 ll BSA (2 mg/ml), 10 pmol of each primer and approximately 100 ng of DNA.…”
Section: Paternity Analysismentioning
confidence: 99%
“…Since then there have been studies on the biology (Saint Jalme et al, 1994;Tieleman et al, 2002), captive breeding (Gélinaud et al, 1997;Hémon et al, 2000) diseases (Ostrowski et al, 1995;Bailey et al, 2008), ecology (van Heezik andOstrowski, 2001), behavior (Gaucher et al, 1996, van Heezik andSeddon, 1998), genetics (Chbel et al, 2002;Idaghdour et al, 2004;Lesobre et al, 2010) and phylogeny (Granjon 95 et al, 1994;Broders et al, 2003) of the Houbara. However, data on the entire growth characteristics of the Houbara is very scant.…”
Section: Introductionmentioning
confidence: 99%